National Health Insurance on Household Out-of-pocket Health Expenses in Indonesia - Ira Yusnita Wijayati; Dwini Handayani (Jurnal Kesehatan Masyarakat, 2025)
BPJS Kesehatan is expected to increase access to fair and high-quality health care for all citizens and provide financial risk protection. Our study aims to examine the impact of BPJS Kesehatan’s implementation as national health insurance (NHI) on household out-of-pocket expenses. Our study used a difference in differences (DID) regression model that was applied to repeated cross-section data from the National Socio-Economic Survey (Susenas) between 2013-2014 and 2019-2020. Propensity-score matching (PSM) is used to provide covariate balance in the regression model data. Illnesses that are represented by health conditions and treatment options (self-medication, outpatient, inpatient) are determining factors of out-of-pocket expenses. Our finding, the implementation of BPJS Kesehatan resulted in a 26.0% increase in out-of-pocket expenses. Its main reason is an increase in public health awareness, as indicated by the increased number of visits to health facilities. However, the increase in out-of-pocket expenses suggests that the usage of BPJS Kesehatan is not optimal. To optimize its function as financial protection, improvements must be made to the mechanism and system policies.